2018
DOI: 10.1016/j.cct.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Positive psychotherapy for smoking cessation enhanced with text messaging: Protocol for a randomized controlled trial

Abstract: Results from this study will provide evidence on whether incorporating positive psychology interventions into smoking cessation treatment can improve smoking cessation outcomes relative to standard behavioral counseling with nicotine patch and text messaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
0
3
0
2
Order By: Relevance
“…Findings indicate that interventions designed to assist both smokers and psychiatric patients in quitting smoking prove to be effective across various countries. While some of these intervention programs used found positive effects on smoking cessation behavior (Amole, Heath, Joshua, & McLear, 2012;Brown et al, 2021;Hecht et al, 2019;Kahler et al, 2015;Kahler et al, 2018;Lee, 2017;Mak, Loke, & Leung, 2021; C. T. Okoli & Khara, 2014; C. T. Okoli et al, 2011;Rajalu et al, 2023), some reported no significant effect and a need to develop more intervention programs (Smits et al, 2019;Smits et al, 2021;Vidrine et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Findings indicate that interventions designed to assist both smokers and psychiatric patients in quitting smoking prove to be effective across various countries. While some of these intervention programs used found positive effects on smoking cessation behavior (Amole, Heath, Joshua, & McLear, 2012;Brown et al, 2021;Hecht et al, 2019;Kahler et al, 2015;Kahler et al, 2018;Lee, 2017;Mak, Loke, & Leung, 2021; C. T. Okoli & Khara, 2014; C. T. Okoli et al, 2011;Rajalu et al, 2023), some reported no significant effect and a need to develop more intervention programs (Smits et al, 2019;Smits et al, 2021;Vidrine et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions like public disposal of cigarette packets and lighters can help remove cues to smoke. Interventions can also include personalized audio, video, or text messages that provide cues to maintain abstinence (Kahler et al 2018). Badges or coins that mark successful abstinence for a set period of time as employed by Alcohol Anonymous may also be used as cues to maintain abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…This additionally suggests that regularly engaging in activities that help maintain relatively high overall levels of positive affect during the initial weeks of a smoking cessation attempt may be beneficial. In line with this idea, prior research suggests that positive psychology-based interventions may be beneficial for both positive affect and smoking cessation (Kahler et al, 2015(Kahler et al, , 2018. Future research would benefit from examining whether just-in-time adaptive interventions designed to boost positive affect can lower the intensity of smoking urges and reduce the likelihood of smoking later in the day when individuals report lower positive affect than their usual in the morning.…”
Section: Morning Positive Affect and Later-day Smoking Urges And Smok...mentioning
confidence: 93%